Synthesis and fluorescence properties of ofloxacin rare-earth nanocomplexes. Issue 1 (February 2020) - Jin, C F; Ren, H X; Du, J; Zhao, Y X; Cheng, Y Q; Wang, C G; Zhou, Z R; Lin, P; Zhao, C; Lv, Y G
Abstract: Two rare-earth complexes with a high fluorescence activity, namely Terbium (Tb)-Ofloxacin(OFLX)-Phenanthroline(Phen) and Europium(Eu)-OFLX-Phen, were prepared. The coordination forms, structure characteristics, and fluorescence properties of the prepared complexes were studied by powder diffraction, infrared spectroscopy, elemental and thermogravimetric analyses. The results show that Tb (OFLX)3 Phen and Eu(OFLX)3 Phen complexes were successfully prepared. The infrared (IR) spectroscopy showed that the ligand of ofloxacin could coordinate with rare-earth Tb (III) or (III) ligands via single and double coordinations. The fluorescence spectra showed that complexes exhibited distinct fluorescence characteristic peaks, which differed from those of ligands. The optimum excitation and emission wavelengths of Tb (OFLX)3 Phen complex were 275 and 545nm, respectively, while those of Eu (OFLX)3Phen were 325 and 614 nm. The fluorescence spectrum revealed that the complex can be used as a fluorescent probe to detect the drug presence. Moreover, the photoluminescence (PL) and electroluminescence (EL) properties of the complexes were studied. The rare-earth complexes formed in this experiment are instrumental in further fluorescent probe applications.